Essay on a series of six cases observed and treated by me in my dispensary practice - Orr, John (The University of Edinburgh, 1941)
[Hand-written]
Essay on a series of six cases observed and treated by me in my dispensary practice: submitted for the Sir Humphry Rolleston Prize